Features and Source Current of Long‐Period Induced Geoelectric Field During Magnetic Storms: A Case Study - S. Y. Wu; S. Yao; X. D. Feng; W. B. Wei; Y. T. Yin; L. T. Zhang; H. Dong; G. W. Wang; J. L. Liu; Y. Q. Yu; D. Wei (Space Weather)
Abstract We present a case study on the long‐period ( >105 s) induced geoelectric field disturbance during magnetic storms. A set of continuous 33‐day measurements of the geoelectric field, geomagnetic field, geomagnetic indices, and interplanetary magnetic field are analyzed. In the studied 33 days, two magnetic storms occurred after 10 geomagnetic quiet days. To exclude the effects from the different underground electrical structures, geomagnetic and geoelectric field measurements from the same ground observatory enrolled in Chinese Meridian Project are studied. Besides, Space Weather Modeling Framework is adopted to calculate the global geomagnetic field disturbances and the contribution from different current systems. The wavelet power spectra analysis reveals that the long‐period geoelectric field disturbance appears only during magnetic storms. Especially, stronger magnetic storm generates weaker geoelectric disturbances at the same observatory. The opposite‐direction eastward geomagnetic field disturbance, which is generated mainly by the field‐aligned current at different magnetic local time, significantly changes the magnitude and direction of the induced geoelectric field via the underground impedance tensor. Therefore, both the effects caused by ring current and field‐aligned current should be considered in analyzing the ground induced geoelectric field. Excluding the effect from the geospace current source, the more accurate electrical conductivity in the upper mantle would be obtained in future.